Information coverage in La República regarding presidentialstatements: The Rolex case - Canchanya Ayala, Alfredo (2025)
This research examines how information about President Dina Boluarte’s statements on the Rolex case was published in the newspaper La República betweenMarch 14 and April 6, 2024. For this study, fundamental criteria such as editorial line, journalistic criteria, and genres considered in the editions published during thatperiod were analyzed. A qualitative approach and a hermeneutic design were chosen. The non-probabilistic sample consisted of 18 editions of the newspaper. Among the most notable findings, the media outlet was identified by its editorial line of opposition to the president. This was demonstrated through the interpretation and opinion included in the published journalistic pieces. Likewise, the media outlet took a position on the president through its editorials and the development of interpretive news stories. La República presented information from a journalistic report to help the public understand how this issue was covered.